Penerapan Model Pembelajaran REACT dalam Peningkatan Pemahaman Konsep Siswa - Aswar Anas; Fitriani A (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2018)
Abstract:Application of the REACT Learning Models in Increasing the Understanding of Students' Concepts. This research is a quasi-experimental research with a class that aims to know: (1) How is the description of students' understanding of mathematical concepts before and after the application of the REACT learning model. And (2) Is there an increase in students' understanding of concepts after the application of the REACT model. In this study using a concept understanding test instrument. From the results of the study, it was concluded that. (1) The application of the REACT learning model can change the average understanding of students' mathematical concepts from low categories to high categories. (2) Increasing understanding of mathematical concepts students on average are in the medium category. And (3) There is an increase in understanding of students' mathematical concepts with the application of REACT learning models.Abstrak:Penerapan Model Pembelajaran REACT dalam Peningkatan Pemahaman Konsep Siswa. Penelitian ini merupakan penelitian eksperimen semu dengan satu kelas yang bertujuan untuk mengtahui: (1) Bagaimana gambaran pemahaman konsep matematika siswa sebelum dan setelah penerapan model pembelajaran REACT. Dan (2) Apakah terdapat peningkatan pemahaman konsep siswa setelah penerapan model REACT. Pada penelitian ini menggunakan istrumen tes pemahaman konsep. Dari hasil penelitian diperoleh kesimpulan bahwa. (1) Penerapan model pembelajaran REACT dapat mengubah rata-rata pemahaman konsep matematika siswa dari kategori rendah menjadi kategori tinggi. (2) Peningkatan pemahaman konsep matematika siswa rata-rata berada pada kategori sedang. Dan (3) Terdapat peningkatan pemahaman konsep matematika siswa dengan penerapan model pembelajaran REACT.